Description of a model tardigrade Paramacrobiotus metropolitanus sp. nov. (Eutardigrada) from Japan with a summary of its life history, reproduction and genomics - Sugiura, Kenta; Matsumoto, Midori; Kunieda, Takekazu (Zootaxa, 2022)
The genus Paramacrobiotus was erected in 2009 from the genus Macrobiotus, and 43 Paramacrobiotus species have been described to date. Although the first genome sequence in the genus was reported for the TYO strain of Paramacrobiotus sp., which is a dioecious species and has five bivalent chromosomes, its precise taxonomic identification remained undetermined. Here, we report its morphology, confirming the presence of a microplacoid, cuticular bulge on the inner side of legs I–III, and granulation on the inner side of legs IV under both light and electron microscopy, and smooth areoles on the egg shell, indicating that it differs from other described species. In addition, the previously described karyotype 2n=10 of this strain is clearly distinct from other species of the genus Paramacrobiotus, supporting the hypothesis that the strain represents a new species. Molecular analyses for the small and large ribosomal subunit (18S rDNA, 28S rDNA), the internal transcribed spacer 2 (ITS-2) and cytochrome C oxidase subunit I (COI) were also performed. The TYO strain is most similar in the analysed nuclear markers to Paramacrobiotus experimentalis Kaczmarek, Mioduchowska, Poprawa & Roszkowska, 2020 and Paramacrobiotus sp. strain MG.002 (p-distances in 18S rDNA: 0.53%, 28S rDNA: 0.98–1.12%, and ITS-2: 9.9%), which corroborates with the overall morphological similarity between these taxa. Despite the close relationship between the TYO strain and P. experimentalis, the genetic species delimitation based on molecular analysis indicates that the TYO strain indeed is a distinct species. Therefore, this tardigrade is described here as Paramacrobiotus metropolitanus sp. nov.